Anopheles gambiae: Metabolomic Profiles in Sugar-Fed, Blood-Fed, and Plasmodium falciparum-Infected Midgut. (17th July 2017) - Champion, Cody J.; Kukutla, Phanidhar; Glennon, Elizabeth K. K.; Wang, Bo; Luckhart, Shirley; Xu, Jiannong
Abstract : The mosquito midgut is a physiological organ essential for nutrient acquisition as well as an interface that encounters various mosquito-borne pathogens. Metabolomic characterization would reveal biochemical fingerprints that are generated by various cellular processes. The metabolite profiles of the mosquito midgut will provide an overview of the biochemical events in both physiological states and the dynamic responses to pathogen infections. In this study, the midgut metabolic profiles of Anopheles gambiae mosquitoes following feeding with sugar, human blood, mouse blood, and Plasmodium falciparum- infected human blood were examined. A mass spectrometry system coupled to liquid and gas chromatography produced a time series of metabolites in the midgut at discrete conditions (sugar feeding, 24 h and 48 h post-normal blood and P. falciparum- infected blood feeding). Triplicates were included to ensure system validity. A total of 512 individual compounds were identified; 511 were assigned to 8 superpathways and 75 subpathways. The dataset can be used for further inquiry into the metabolic dynamics of sugar and blood digestion and of malaria parasite infection. The dataset is accessible at the repository Dryad.